Percentage of horses with IgE levels above the cut-off values following import from Iceland to Switzerland. - Jasmin Birras (11707271); Samuel J. White (10512181); Sigridur Jonsdottir (1303788); Ella N. Novotny (11707274); Anja Ziegler (11707277); A. Douglas Wilson (11707280); Rebecka Frey (3362939); Sigurbjörg Torsteinsdottir (11707283); Marcos Alcocer (8212260); Eliane Marti (157764) (2021)
Horses with IgE levels above the cut-off values (as indicated in Table 2 ) at time of clinical onset of IBH (T IBH ), one year before (T IBH -1)) and one year after (T IBH +1) and in healthy horses for comparison. P values were calculated with the Fisher’s exact test and Bonferroni correction done for multiple comparisons. * significant difference between T IBH and T IBH-1 (cP < 0.05). ** significant difference between T IBH -1 and H (cP < 0.05).